CARBON ISOTOPIC COMPOSITION OF THE HYDROCARBON FLUIDS OF THE SOUTH CASPIAN MEGADEPRESSION - Guliev I.S.; Feizullaev A.A.; Guseinov D.A. (My University, 2001)
Carbon isotopic composition was studied in oils and hydrocarbon gases from different oil and gas fields and reservoirs hosted in the Upper Cretaceous to Upper Pliocene sequences of the South Caspian mega-depression. It was established that the carbon isotopic composition becomes gradually heavier in oils and lighter in hydrocarbon gases of reservoirs in accordance with decreasing age of the host sediments. Based on these revealed trends, the Pliocene reservoirs contain mixed oils generated by Paleogene–Lower Miocene and Diatomaceous (Middle–Upper Miocene) deposits, as well as oil produced within one stratigraphic complex. Using isotope tracers, the contributions of the Paleogene–Lower Miocene and Diatomaceous oils in the Pliocene reservoirs were estimated. The central part of the studied region is promising for the discovery of future hydrocarbon accumulations.
Keywords: Miocene; Pliocene; Paleogene; Cretaceous; Cenozoic::Neogene::Miocene; Cenozoic::Neogene::Pliocene; Cenozoic::Paleogene; Mesozoic::Cretaceous; Мезозой::Меловая; Кайнозой::Палеоген; Кайнозой::Неоген::Миоцен; Кайнозой::Неоген::Плиоцен